COMMUNAL LAND CONFLICTS AND STATE RESPONSE IN NIGERIA: A STUDY OF AMASIRI–OSO (EDDA) CRISIS IN EBONYI STATE, NIGERIA - UROM, Charles Egwu (PT. Antis International Publisher, 2026)
Objective: The communal land conflict continues to be a problem in Nigeria which affects governance, security and socio-economic development especially in agrarian communities. This study deals with the Amasiri–Oso (Edda) crisis in Ebonyi State to analyse the dynamics of communal land dispute, and evaluate the effectiveness of state response to this crisis. While these conflicts can be traced back to historical and cultural background, the prolonged existence of such conflicts do raise critical issues concerning the capacity of states, institutional legitimacy and sustainable conflict management. Method: Qualitative research design, semi-structured interviews, and secondary data sources (government reports, media accounts, and scholarly literature) were used in this study. Thematic and content analysis were used to analyse the data and find patterns in conflict drivers and state intervention strategies. The analysis draws on State Capacity Theory that theorizes the importance of constraints on institutional coordination, enforcement, and legitimacy on the outcomes of governance in conflict settings. Results: The results indicated that historical uncertainties of land ownership, socio-economic stress on land, political manoeuvres and identity claims are the forces driving the conflict. Reactive responses, such as deployment of security forces, administrative measures and lack of effective inter-agency coordination, have been inadequate to address root causes. Legitimacy and effectiveness of interventions are further undermined by perceptions of bias, lack of integration of traditional conflict resolution mechanisms and implementation gaps. The conflict also has an impact on the governance of the area, loss of trust in institutions, displacement, loss of livelihoods and reduced productivity. Novelty: The research finding is the need to move from reactive crisis management to integrated and preventive approaches to conflict resolution for sustainable outcomes. It calls for improved land governance, institutionalised hybrid conflict resolution mechanisms, better inter-agency coordination, as well as conflict-sensitive development policies for lasting peace and governance stability.